Causal relationship between Depression and Health-related quality of life through chain mediation of Chronic Fatigue and Treatment Adherence in women with uterine cancer - Sakkaki, Sedigheh; Naderi, Farah; Hafezi, Fariba (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of the present study was to investigate the causal relationship between depression and health-related quality of life through the chain mediation of chronic fatigue and adherence to treatment in women with uterine cancer. Method: In this descriptive correlational study, the statistical population consisted of all women diagnosed with uterine cancer in Mashhad in the year 2021, and 261 people were selected as a sample by purposive sampling. In this study, Health-related quality of life of Weber (1992), Depression of Beck (1996), Chronic fatigue of Chalder et al (1993), Treatment Adherence of Seyyed Fatemi, Rafiei, Hajizadeh & Madanlo (2018) were used for data collection in this study. The data were analyzed using Pearson’s correlation coefficient and path analysis model with the help of SPSS-27 and AMOS-25 software. Results: The findings showed the relationship between depression and health-related quality of life; between depression and chronic fatigue; between chronic fatigue and adherence to treatment; There was a significant relationship between adherence to treatment and health-related quality of life (p<0.01); Also, the indirect path of depression with health-related quality of life with the mediating role of chronic fatigue and adherence to treatment were significant (p<0.01). Conclusion: Based on the results of this research, the proposed model had a favorable fit and is considered an important step in the direction of knowing the factors affecting the quality of life related to the health of women with uterine cancer.